Harnessing Artificial Intelligence in Mentimeter Based Interactive Learning Media to Enhance Students' Numeracy Literacy - Pradipta Annurwanda; Ellissi, Wike; Maerz, Maximilian (Hipotenusa: Journal of Mathematical Society, 2024)
According to the 2022 PISA results, Indonesia's mathematical literacy score dropped by 13 points to 366, placing it 106 points below the global average. This decline is closely tied to students' numerical literacy skills. To address this, learning should encourage students to solve mathematical problems through critical, logical, and creative thinking. Interactive learning media that meets students' needs is essential to enhance numerical literacy. The objective of this study is to develop artificial intelligence-based interactive learning media, specifically using Mentimeter, to improve students' numerical literacy skills. The research follows the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation), with data collected through questionnaires and tests. The success indicators for the media include a minimum of valid for validity, practical for practicality, and high for effectiveness. The results show that the Artificial Intelligence-based interactive learning media was successfully developed. The validity test averaged 93.74% in the "very valid" category, the practicality test averaged 90.14% in the "very practical" category, and the effectiveness test yielded an N-Gain Score of 0.71 (71.09%), classified as "high." These findings demonstrate that AI-based interactive learning media can significantly improve students' numeracy literacy skills.